The study on the recovery of magnesium sulfate from bittern - Alfonso, Cecile F.; Gelera, Leonora P.; Cocjin, Pilarita (1982)
The feasibility using the chemical treatment method for recovery of magnesium sulfate from bittern, a waste from the crystallization of sodium chloride from concentrated sea water, was investigated. The effects of processing parameters namely: concentration of alkal and acid as precipitant and solubilizer, the density of magnesium sulfate, and the temperature of crystallization were determined. Under optimum conditions, approximately 96.54% of magnesium sulfate was recovered from bittern employing the chemical treatment method.